Self Management Siswa dalam Belajar Online di SMAN 1 Kuantan Hilir - Al-Qadri, Arif; Rahmi, Alfi (Indonesian Research Journal on Education, 2022)
This research is motivated by the problems that occur in students at SMA 1 Kuantan Hilir in theonline learning process. The problems in question are related to self-management, such as selfmotivation, self-organization, self management and self-development, such as time management, place setting and great interest in learning. The purpose of this study was to determine the level of mastery of students' self management in online learning.The type of research conducted is descriptive quantitative research by describing, describing and interpreting events in accordance with the facts obtained, the results are in the form of numbers. The population in this study was 88 students, the samples taken were all of the number of students in class XI IPS using total sampling technique. The results of the study obtained that self management of students in online learning atSMA 1 Kuantan Hilir was based on 4 indicators, three of which were in the medium category witha percentage of 50% and one of them was in the low category with a percentage of 33.33%.Therefore, the indicator in the low category is the self-compilation indicator, this is due to theassumption/thought among students that the learning process that occurs during the Covid-19pandemic is not what they want. This means that the school must understand all the limitationsthat exist, especially those experienced by students. The impact of this, students hope that the teacher continues to give the best (value) to them so that they do not feel disadvantaged. Students do not try to organize themselves (organization/management) of independent learning to compensate for the shortcomings that exist during the learning process.